The Relationship Among Community Based Tourism Application, Community Attitude, Community Empowerment and Community Life Satisfaction - Piartrini, Putu Saroyini (E-Journal of Tourism; Volume 5 Number 2 (September 2018), 2018)
Tourism involves the movement of individuals from one region to another, which are sometimes of different cultures. The interaction between tourists and local communities in tourist destinations is social interaction. The community does not always react positively to the development of certain destinations or attractions. Public attitudes that are not always beneficial to tourism have various causes, such as the well-being differences that appear so starkly between wealthy tourists and poor local communities and  conflict over limited resources such as water, land and cultural resources. This condition needs to be addressed because frequent demonstrations at various tourist attractions in Bali may jeopardize the security and comfort of tourists and affect the image of Bali as an international tourist destination. This study aims to: 1) To evaluate local government policies in community empowerment; 2) To measure perceived community-based tourism implemented   in the destination areas 3) To measure thelife satisfaction of the people in tourist destinations; 3)To measure individual   attitude toward toursm develoment  in Destinations. The results of this study are expected to be useful as input in the formulation of regional tourism policies  to realize tourism development goals effectively. This study is different from previous tourism studies because it examines the impact of tourism development from an integral perspective of sustainable tourism and community-based tourism.   Keywords: community attitude, community-based tourism, community empowerment, community life satisfaction.